Sixteenth International Conference on Quality Control by Artificial Vision 2023
DOI: 10.1117/12.2692384
|View full text |Cite
|
Sign up to set email alerts
|

We can pass through the wall gap: aperture passage perception via vibration stimuli generated from distance variation

Shinichiro Morita,
Yuki Kikuchi,
Akira Saeki
et al.

Abstract: We have been developing a helmet-type spatial perception support system that provides the user with vibration stimuli in response to the distance variation to an obstacle. The purpose of this research is set to propose a method for generating vibration stimuli that appropriately represent two environmental elements, walls and apertures, and verify its effectiveness for the aperture passage perception. The five vibro-motors are positioned at directional angles of 0 degree in front, 30 and 60 degrees to left and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…So far, we have confirmed that when the blindfolded user wearing the VieW is walking without relying on vision, the user can perceive space based on the vibration provided to the user, such as localization of obstacles in front, detection and passage through aperture [4] [5]. In an experiment in which the subject was asked to perform a walking task while avoiding collisions in an environment that simulated a corridor with walls on only one side, it was confirmed that the subject was able to recognize the wall on one side and walk along the wall.…”
Section: Introductionmentioning
confidence: 53%
“…So far, we have confirmed that when the blindfolded user wearing the VieW is walking without relying on vision, the user can perceive space based on the vibration provided to the user, such as localization of obstacles in front, detection and passage through aperture [4] [5]. In an experiment in which the subject was asked to perform a walking task while avoiding collisions in an environment that simulated a corridor with walls on only one side, it was confirmed that the subject was able to recognize the wall on one side and walk along the wall.…”
Section: Introductionmentioning
confidence: 53%